FOUNDATION ENGLISH AT THE UNIVERSITY OF VENDA: HOW RESPONSIVE IS IT? - Kaburise, P (South African Journal of Higher Education, 2016)
This paper, first, identifies the reading characteristics of students enrolled in the foundation provision of the extended degree; then determines the responsiveness of the English curriculum to these characteristics and thinking on literacy development. Using both qualitative and quantitative research methods, and the language ability framework of Bachman and Palmer (1996), a placement test was given to these students and their reading characteristics were isolated. Next, these characteristics were compared to the English curriculum to determine how responsive its contents are to these attributes and literacy development. The results show that students are competent in certain types of comprehension activities, vocabulary manipulation but have difficulties interacting with texts particularly determining relationships between sentences and sections of texts. The results of the second part indicate that the curriculum follows an autonomous concept of language support and only parts of the English curriculum are responsive to the students’ reading characteristics.